2018
DOI: 10.1002/anie.201800909
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of 2‐Deoxyglycosides from Glycals by Visible‐Light‐Induced Photoacid Catalysis

Abstract: The direct, photoacid-catalyzed synthesis of 2-deoxyglycosides from glycals is reported. A series of phenol-conjugated acridinium-based organic photoacids were rationally designed, synthesized, and studied alongside the commercially available phenolic catalyst eosin Y. In the presence of such a photoacid catalyst and light, synthetic glycals were activated and coupled with a range of alcohols to afford 2-deoxyglycosides in good yields and with excellent α-selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 93 publications
1
84
0
Order By: Relevance
“…[11] And the results implied that 1 icould not acquire a single electron from photoexcited state of eosin Y. Furthermore, the fluorescence quenching experiments also confirmed that the oxidation of alcohols (not only unactivated primary alcohol but also benzyl alcohol) was not induced by an electron transfer process ( Figure 1B According to the experiments above and previous reports, [12] a possible HAT mechanism for visible-light-promoted aerobic oxidation of primary alcohols and formation process of the quinazolinones is suggested in Scheme 6. Initially, eosin Y (EY) reaches its excited state EY* in biradical form under irradiation of visible light.…”
Section: Resultssupporting
confidence: 71%
“…[11] And the results implied that 1 icould not acquire a single electron from photoexcited state of eosin Y. Furthermore, the fluorescence quenching experiments also confirmed that the oxidation of alcohols (not only unactivated primary alcohol but also benzyl alcohol) was not induced by an electron transfer process ( Figure 1B According to the experiments above and previous reports, [12] a possible HAT mechanism for visible-light-promoted aerobic oxidation of primary alcohols and formation process of the quinazolinones is suggested in Scheme 6. Initially, eosin Y (EY) reaches its excited state EY* in biradical form under irradiation of visible light.…”
Section: Resultssupporting
confidence: 71%
“…Meanwhile, 1 betaine shows delocalization of the HOMO and LUMO, which leads to the changes in the absorption spectrum,s howinganewp eak around5 30 nm (FigureS4i nt he Supporting Information). The thermodynamic feasibility of the eT between the donora nd acceptoru nits was verified by estimating the free-energy change of eT according to Equation (1): [20] DG Figure 1C shows the fluorescences pectra of 1-3,w hich provide insights into the transientp athways in the photoexcitation.…”
Section: Resultsmentioning
confidence: 99%
“…The shape of this peak resembles that of the peak obtained from the differences teady-state absorption spectrum between 1 and 1 betaine ( Figure S4 in the Supporting Information), which corresponds to the characteristicp eak of the betaine. Eur.J.2020, 26,[2060][2061][2062][2063][2064][2065][2066] www.chemeurj.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim structures imilar to 1, [20] comprising acridinium and phenolic moieties, can be deprotonated on illumination and act as a photoacid. The betaine form can evolve as the result of the photoinduced intramolecular eT (Figure2E), whichi sf ollowed by deprotonation of the phenolic OH group, and af ast intramolecular eT could not be observed in the time resolution of our experimental apparatus( > 10 ns).…”
Section: Resultsmentioning
confidence: 99%
“…It has mostly been employed as a SET oxidant or reductant upon conversion to its excited state by visible‐light irradiation. Interestingly, the Wang group recently reported that photoexcited eosin Y could function as phenolic acid to catalyze the direct addition of alcohols to glycols, allowing stereoselective synthesis of 2‐deoxyglycosides (Scheme a) . In contrast, Wu and co‐workers identified photoexcited eosin Y as a direct hydrogen atom transfer (HAT) catalyst to enable general alkylation of C−H bonds with electron‐deficient alkenes .…”
Section: Introductionmentioning
confidence: 99%